Self-activation by a C-terminal domain arginine finger regulates GTP hydrolysis in bacterial zinc metallochaperones - Joseph S. Rocchio; Maximillian K. Osterberg; Emma M. McRae; Nancy Jaiswal; Katherine A. Edmonds; D. Annie Doyle; Eric P. Skaar; David P. Giedroc (Proceedings of the National Academy of Sciences, 2026)
The cellular response to transition metal scarcity is multifaceted and complex. Members of the Cluster of Orthologous Groups 0523 (COG0523) superfamily are proposed to chaperone a bound metal to activate an apoenzyme client and are thus candidate metallochaperones. COG0523 enzymes are GTPases that harbor a conserved Ras-like guanosine-5‘-triphosphate (GTP)-binding and hydrolysis domain (G-domain) and a C-terminal domain (CTD) of unknown function connected by a flexible linker. AlphaFold3 modeling posits an “open” GTPase-inactive and “closed” GTPase-active conformation where the GTP and switch 1 (G2) loop are buried at the interface of the two domains. We show here that the CTD functions as a GTP-hydrolysis activation protein (GAP) domain that stimulates GTP hydrolysis by the tethered G-domain. This “self-activation” requires an invariant RxK sequence in the β2-strand of the CTD in two distantly related bacterial COG0523s from Acinetobacter baumannii , ZigA and MigC. Thermodynamic and kinetic studies reveal that the Arg is analogous to the arginine finger motif of a Ras-cognate GAP, while the Lys residue appears to play a catalytic role in GTP hydrolysis. Cognate CTD added in trans to full-length RxK mutant ZigA or MigC rescues Zn(II)-activated GTPase activity whereas the noncognate CTD shows no rescue. The linker in Ab ZigA appears to gate Zn(II)-stimulated GTP hydrolysis. Solution NMR studies of RxK Ab MigC reveal that the two domains tumble independently of one another in the absence of bound ligands, with cognate CTD added in trans forming a tight complex. The extent to which conformational switching characterizes eukaryotic COG0523s is discussed.